Perlindungan Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Cabul Studi Putusan Pengadilan Negeri Sungguminasa No.8/Pid.Sus-Anak/2017/PN.Sgm - Vinamya Audina Marpaung; Madiasa Ablisar; Marlina Marlina; Edi Yunara (Universitas Sumatera Utara, 2019)
Abstract. Children are the next generation of generation and successors of existing development struggles. Children are the mandate as well as the gift of God Almighty that we always have to guard because in him the dignity, dignity and rights as human beings must be upheld. Child rights are part of human rights contained in the 1945 Constitution and the United Nations Convention on the Rights of the Child. Criminal acts of sexual abuse committed by children in the Sungguminasa District Court No.8 / Pid.Sus-Anak / 2017 / PN.Sgm. Stating the child above, has been proven legally and convincingly guilty of committing a criminal act